Characteristics of near-nozzle spray development from a fouled GDI injector. (1st May 2018) - Zhou, Jianwei; Pei, Yiqiang; Peng, Zhijun; Zhang, Yanfeng; Qin, Jing; Wang, Li; Liu, Changwen; Zhang, Xiaoyu
Highlights: Fuel nozzle deposits were characterized. Near-nozzle spray characteristics of new and fouled injectors were compared. The effects of deposits on spray characteristics were analyzed. Nozzle fouling decreased the fuel flow rate, plume width and spray area. Deposits may cause residual fuel, tip wetting, plume disintegration and liquid splash. Abstract: The near-nozzle spray development of a typical fouled gasoline direct injection (GDI) injector was investigated. The fouled injector had been used in a stratified-charge combustion GDI engine and showed typical characteristics, such as accumulated deposits inside and around the nozzles and a reduced flow rate of 2.9–5.7%. Back-illumination and Mie-scattering methods were employed in spray experiments, in conjunction with a high speed camera and a macro lens, to assess the near-nozzle spray behaviors. The experimental results show that at all injection pressures tested, the interaction between deposits and spray led to several poor spray behaviors during the full injection evolution, including spray distortion, residual fuel storage in the nozzles and deposits layer, liquid splashing, the formation of ligament and large droplets and tip wetting/dripping. These effects all may result in high soot emissions. The after-injection stage of the fouled injector produced more liquid ligaments than that of the new injector. It was also found that high injection pressures did not improve atomization during after-injection, nor reduce the amounts of ligaments and droplet clusters beyond the main spray boundary. The plume width and projected spray area of a single nozzle in the fouled injector were decreased by 5–7% and 17–20%, respectively, due to fuel flow losses. The delays in the start of injection and end of injection were approximately 20 μs and 30–40 μs, respectively.